Achilles Tenorrhaphy in Five Dogs: A Modified Surgical Technique and Evaluation of a Cranial Half Cast - Guerin, S.; Burbidge, H.; Firth, E.; Fox, S. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
Achilles mechanism rupture in four of five dogs was treated with tenorrhaphy using a modified surgical technique designed to optimise accurate apposition of tendon to bone. Two bone tunnels were drilled in the calcaneal tuber from a plantomedial - dorsolateral, and plantolateral – dorsomedial direction respectively. The distal ends of the tendons were sutured to the calcaneal tuber using a Krachow suture pattern. The remaining dog had a mid-tendon Achilles mechanism rupture. A resinous half cast was placed on the cranial aspect of the tarsocrural joint of all five dogs, for a minimum of six weeks, in order to provide limited post operative support. Du e to insufficient cast material two of the support splints failed and one of these cases also required a second surgical procedure. A varying amount of soft tissue irritation was noted in each case. All of the five Achilles mechanisms healed, and all of the dogs returned to normal function.Five dogs with surgical reconstruction of the Achilles mechanism were stabilised postoperatively with a resinous half cast placed on the cranial aspect of the tarsocrural joint for a minimum of six weeks. Two of these casts failed at the tarsocrural joint when six folds of casting material were used; all subsequent cases had eight folds applied. Variable soft tissue irration was observed under the cast in each case. A modified surgical technique using a Krachow suture pattern allowed good tendon-bone apposition. All five Achilles mechanisms healed, and all dogs returned to normal function. Bilateral lesions were identified in 3 of the 4 dogs examined.
Keywords: Achilles mechanism; Achilles repair; cranial half cast